4. CORONARY CALCIUM SCORE, RATHER THAN CAROTID INTIMA-MEDIA THICKNESS, IS MORE PREDICTIVE OF CORONARY RESTENOSIS AFTER DES IMPLANTATION - Yun-Seok Choi (Artery Research, 2009)
Background: Calcium scoring on MDCT and carotid intima-media thickness (IMT) have been widely used as indices of atherosclerosis. However, the clinical correlation between carotid IMT and the severity of coronary artery disease (CAD) is relatively poorly established. The aim of this study was to determine the relation between coronary restenosis after DES implantation and carotid IMT. Methods: Among a total of 3041 patients who underwent carotid ultrasonography, 956 patients (male:female=583:373, mean age=61±11 years) with DES implantation who had undergone follow-up coronary angiography were divided into two groups. Group 1 (n=861, male=61%, mean age 60±11 years) was the no ISR group. Group 2 (n=95, male=67.4%, mean age=65±9 years) was the ISR group. ISR was defined as a more than 50% reduction in luminal stent diameter on follow-up coronary angiography. Carotid IMT was measured using a 15MHz high frequency transducer on the far walls of both carotid arteries. Intimal thickness, defined as high echogenic thickening in the intimal area on carotid ultrasound, was also measured. The calcium score on MDCT was also compared between the two groups. Results: On comparison between the two groups (group 1 vs group 2), 1. The right mean IMT and media thickness were larger in Group 1 (p=0.023, p=0.048). 2. There was no significant difference in the right and left maximal IMT or left medial thickness (Table). 3. Calcium scores were significantly higher on MDCT in the ISR group (427±86 vs 1599±482, p<0.05). On multivariate analysis after adjustment for age, the calcium score on MDCT was the strongest predictor of coronary artery restenosis (odds ratio 1.3, p=0.027, 95% CI:1.02–1.89). Conclusion: The coronary calcium score is a better predictive marker for stent restenosis after DES implantation when compared to the carotid IMT. Noninvasive measurement of the calcium score and carotid IMT might be useful for evaluation of coronary restenosis.